PENERAPAN METODE COOPERATIVE SCRIPT DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN UNTUK MENINGKATKAN DAYA INGAT SISWA KELAS V DI SD NEGERI 2 MAKALE UTARA - Berti Berti; Erniati Erniati; Risma Risma (CV. Adiba Aisha Amira, 2023)
The problem in this study is that when the teacher gives questions, both questions directly related to previous learning or in the form of questions, where only a few students can provide answers without reopening notes or looking at printed books. The purpose of this study was to find out whether the application of the Cooperative Script method in PAK learning could improve the memory of fifth grade students at SD Negeri 2 Makale Utara. The theory used in this study uses the theory developed by Kemmis & Mc.Taggart which consists of research settings, research action plans, achievement indicators, instruments used, data collection techniques, and data analysis techniques. Cycle I at the first meeting students who were in the good category reached 50%, at the second meeting students who were in the good category reached 63.63%. while cycle II which was carried out in one meeting reached 86% and had achieved the predetermined success indicators.